The Role of Nanomaterials as Effective Adsorbents and Their Applications in Wastewater Treatment - Sadegh, Hamidreza; Ali, Gomaa A. M.; Gupta, Vinod Kumar; Makhlouf, Hamdy Abdel Salam; Ghoshekandi, Ramin Shahryari; Nadagouda, N. Mallikarjuna; Sillanpaa, Mika; Megiel, Elzbieta (Springer, 2017)
Nanomaterials have been extensively studied for heavy metal ions and dye removals from wastewater. This article reviews the role of nanomaterials as effective adsorbents for wastewater purification. In recent years, numerous novel nanomaterial adsorbents have been developed for enhancing the efficiency and adsorption capacities of removing contaminants from wastewater. The innovation, forthcoming development, and challenges of cost-effective and environmentally acceptable nanomaterials for water purification are discussed and reviewed in this article. This review concludes that nanomaterials have many unique morphological and structural properties that qualify them to be used as effective adsorbents to solve several environmental problems.